PEDIATRIC URINARY INFECTIONS, CAUSED BY EXTENDED-SPECTRUM BETA-LACTAMASE - PRODUCING MICROORGANISMS IN VARNA, BULGARIA - Neli M. Ermenlieva; Dimitrichka D. Bliznakova; Gabriela S. Tsankova; Tsvetelina K. Popova; Emiliq P. Georgieva; Tatina T. Todorova (Peytchinski Publishing, 2016)
Background: Extended-spectrum beta-lactamase (ESBLs) producing bacteria are microorganisms which have the ability to hydrolyze β-lactame ring of a large part of the antibiotics, commonly used to treat bacterial infections including urinary tract infections. Purpose: The aim of this study is present the epidemiology of childhood urinary tract infections caused by ESBL-producing strains in Varna, Bulgaria. Material/methods: A total of 3895 urine samples of children patients (aged 0 to 18 years) were examined during the period 2010-2012 for presence of ESBL-producing bacteria. Results: Six percent of the tested urinary samples were positive for ESBL production. All of the isolates were resistant to ampicillin, piperacillin, cephalothin, cefprozil, cefuroxime, ceftriaxone, ceftazidime, levofloxacin, cefaclor, but were were sensitive to meropenem and imipenem. Conclusions: Cephalosporins and penicillins are the most used antibiotics in Bulgaria, but they should be very precisely prescribed in medical practice, because otherwise preconditions for maintaining high share of ESBLs are created.